Nighttime observation and chemistry of HOx in the Pearl River Delta and Beijing in summer 2006 - Lu, Keding; Rohrer, Franz; Holland, Frank; Fuchs, Hendrik; Brauers, Theo; Andreas Oebel; Ralph Dlugi; Min Hu; Xin Li; Shengrong Lou; Min Shao; Zhu, Tong; et al. (Atmospheric Chemistry and Physics, 2014)
Nighttime HOx chemistry was investigated in two ground-based field campaigns (PRIDE-PRD2006 and CAREBEIJING2006) in summer 2006 in China by comparison of measured and modeled concentration data of OH and HO2. The measurement sites were located in a rural environment in the Pearl River Delta (PRD) under urban influence and in a suburban area close to Beijing, respectively. In both locations, significant nighttime concentrations of radicals were observed under conditions with high total OH reactivities of about 40-50 s(-1) in PRD and 25 s(-1) near Beijing. For OH, the nocturnal concentrations were within the range of (0.5-3) x 10(6) cm(-3), implying a significant nighttime oxidation rate of pollutants on the order of several ppb per hour. The measured nighttime concentration of HO2 was about (0.2-5) x 10(8) cm(-3), containing a significant, model-estimated contribution from RO2 as an interference. A chemical box model based on an established chemical mechanism is capable of reproducing the measured nighttime values of the measured peroxy radicals and k(OH), but underestimates in both field campaigns the observed OH by about 1 order of magnitude. Sensitivity studies with the box model demonstrate that the OH discrepancy between measured and modeled nighttime OH can be resolved, if an additional ROx production process (about 1 ppb h(-1)) and additional recycling (RO2 -> HO2 -> OH) with an efficiency equivalent to 1 ppb NO is assumed. The additional recycling mechanism was also needed to reproduce the OH observations at the same locations during daytime for conditions with NO mixing ratios below 1 ppb. This could be an indication that the same missing process operates at day and night. In principle, the required primary ROx source can be explained by ozonolysis of terpenoids, which react faster with ozone than with OH in the nighttime atmosphere. However, the amount of these highly reactive biogenic volatile organic compounds (VOCs) would require a strong local source, for which there is no direct evidence. A more likely explanation for an additional ROx source is the vertical downward transport of radical reservoir species in the stable nocturnal boundary layer. Using a simplified one-dimensional two-box model, it can be shown that ground-based NO emissions could generate a large vertical gradient causing a downward flux of peroxy acetic nitrate (PAN) and peroxymethacryloyl nitrate (MPAN). The downward transport and the following thermal decomposition of these compounds can produce up to 0.3 ppb h(-1) radicals in the atmospheric layer near the ground. Although this rate is not sufficient to explain the complete OH discrepancy, it indicates the potentially important role of vertical transport in the lower nighttime atmosphere.